Tax administration system: a study on the efficiency of Malaysian indirect taxes - Mansor, Muzainah; Tayib, Mahamad; Yusof, Rohana @ Norliza (Inderscience Enterprises Ltd., 2005)
This study examines the capabilities of the current Malaysian indirect tax administration system as one of the fiscal infrastructures in facing the challenges of globalization and trade liberalisation.The results revealed that Malaysian Customs Department had been collecting less indirect taxes revenue each year as compared to the costs incurred in collecting the revenue. The ratio analysis of total arrears to total revenue collected indicated that uncollected indirect tax revenues are on the increasing trend.The finding also indicated that the tax administrative arrangements should be improved to make the system relatively more efficient and effective.The result further indicated that the perception of the employees for both departments towards their commitment is high and statically equivalent.